Identifikasi Rancang Bangun Alat Ukur dan Sistem Kendali Kadar Total Dissolved Solid (TDS) Pada Air Berbasis Mikrokontroller - Mohammad Hafiz Hersyah (Universitas Andalas, 2017)
In this study, the total dissolved solid (TDS) in water was made using conductivity sensor which the sensor works by using the principle of conductance that is the ability of the solution in delivering the electric current, so the more content of solute contained in the water the greater also the value of its conductance. The measurement results of the sensor will be compared with the next setpoint value will be used to turn on the booster pump which will do the filtering process in order to decrease the TDS water content by using RO membrane. The performance of sensor readings when first used is boosted by the time at which the system takes 3 minutes to reach a stable state, while for the whole system is influenced by the volume of water that will decrease its TDS level. The test results are presented in the form of graph of change of TDS water content over time, the difference of time required to decrease the TDS level by 15 ppm for 1 liter of water for 6 minutes, 2 liter of water for 10 minutes and for 3 liters of water for 16 minutes.